2014
DOI: 10.1111/ejh.12275
|View full text |Cite
|
Sign up to set email alerts
|

External validation and clinical evaluation of the International Prognostic Score of Thrombosis for Essential Thrombocythemia (IPSET‐thrombosis) in a large cohort of Chinese patients

Abstract: We validate the reproducibility of IPSET-thrombosis in Chinese ET patients and provide key clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
3
20
2
1
Order By: Relevance
“…15 In the future, however, some authors already believe that the IPSET-thrombosis classification will be incorporated to stratify patients with ET. 8,9,16 The demographic characteristics, clinical and laboratory parameters of our sample of patients are similar to those described in the literature. 3 Hemorrhagic events were less prevalent than the thrombotic ones also in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…15 In the future, however, some authors already believe that the IPSET-thrombosis classification will be incorporated to stratify patients with ET. 8,9,16 The demographic characteristics, clinical and laboratory parameters of our sample of patients are similar to those described in the literature. 3 Hemorrhagic events were less prevalent than the thrombotic ones also in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 61%
“…[17][18][19] Additionally, in agreement with other authors, we found a significant association between splenomegaly and venous thrombosis, and cardiovascular risk factors and a high WBC with arterial thrombosis. 1,7,8,10,16 Interestingly, age ≥ 60 years in our cohort of patients was not a significant risk factor for thrombosis. The lack of correlation between older age and thrombosis was also seen in other recent studies such as those of Lekovic et al 1 and Montanaro et al 20 The presence of JAK2 mutation was not significantly associated with thrombosis in our study, contrary to information well-established in the literature.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Barbui et al 17 included patients from European countries and the United States as a validation cohort in this study. Fu et al 18 reported the results of their study, which validated the scoring system in a Chinese patient cohort. Conversely, Angona et al 21 failed to validate the system in a single-center setting in a Spanish patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…17 The IPSET-Thrombosis score was validated by an internal and external validation set. Most recently, Fu et al 18 V617F mutation frequency in Turkish patient cohorts compared to other patient populations, and they have also documented an increased risk of thrombosis in JAK2 V617F mutationepositive ET patients. To date, the reproducibility of the IPSET-Thrombosis score compared to the conventional scoring system has not been reported in a Turkish population.…”
Section: Introductionmentioning
confidence: 99%